The Impact of Freezing Time of Chicken Carcass on Chemical Composition, Antioxidant Properties, and Organoleptic Value of Taliwang Chicken Dishes - Endang Agustini; Bulkaini Bulkaini; Djoko Kisworo; Fahrullah Fahrullah; Novizar Nazir; Bidura Bidura (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The Taliwang chicken dish has been one of the most popular dishes on Lombok Island since the Selaparang Kingdom. This study aims to determine the effect of the length of time chicken carcasses are frozen on the chemical composition, antioxidant levels, and organoleptic value of Taliwang chicken dishes. The materials used were the carcasses of 20 superior Balitbangtan native chickens aged 6 weeks, as well as several natural spices and chemicals, to test the chemical characteristics, antioxidant levels, and organoleptic properties of Taliwang chicken dishes. The research was conducted using an experimental method based on a completely randomised design with a one-way pattern, with four treatments of frozen storage time (days): L0 = no storage; L1 = 2 days; L2 = 4 days; and L3 = 6 days, with five replications. The research variables, such as chemical composition, were analysed using the proximate method; antioxidant levels were analysed using the DPPH method; and organoleptic evaluation was analysed using the sensory test method. The research data were analysed using analysis of variance, followed by Duncan's test, in SPSS version 25. The results showed that the length of frozen storage had a very significant effect (P < 0.01) on the antioxidant content and organoleptic value of Taliwang chicken dishes, but no significant effect (P > 0.05) on the protein, fat, or water content. The protein content of Taliwang chicken dishes, based on the length of frozen storage, ranged from 27.25% to 28.57%; the antioxidant content ranged from 64.62% to 95.75%; and the dishes were classified as having a delicious aroma, taste, and texture. The optimal storage period for chicken carcasses before processing is 4 days, yielding an antioxidant content of 95.75%. The nutritional content and organoleptic properties indicate that Taliwang chicken dishes remain suitable for consumption. Contribution to Sustainable Development Goals (SDGs)SDG 2 – Zero HungerSDG 3 – Good Health and Well-BeingSDG 12 – Responsible Consumption and Production